Histórias de vida e saberes de professores de educação física que atuaram nos anos iniciais do ensino fundamental nas décadas de 1980 e 1990 - Costa, Catia Silvana da (Universidade Federal de São Carlos, 2017)
Based on the oral narratives of Antônio Carlos, Romilda Augusta and Dinalva Aparecida, retired Physical Education teachers, in this PhD research, we analyze their life histories in the construction of the teaching knowledge in the context of the initial years of Elementary School of the state education network in the 1980s and 1990s. We chose life histories as a qualitative research, with the use of in-depth and open interviews and documentary analysis. We explain the search and selection process, the profiles of the participants and the process of construction of the analysis themes. The themes - related to the teaching knowledge that emerged from the extracurricular, school, training and professional trajectories of teachers - also settled on the data themselves and made real the possibility of apprehending several stories in the same history of life. In order to develop the aforementioned objective, themes and data analysis, we will discuss life histories, teacher knowledge and identity, teaching learning, reflection possibilities based on life histories and the context of formation - based on a curricular model "traditional-sports" - of teachers in Santo André and Bauru and of professional performance in several schools of public and private education networks in the State of São Paulo. The influence of some tendencies and the technization of Physical Education, the dependence between the reminiscences of the different trajectories of the teachers and the family, social, scholastic, religious and professional relations of each one of them and the focus in the first moment of the History of Physical Education in the State of São Paulo, where his classes were taught by a specialist teacher in the initial years, were also, among others, the object of these dialogues. We have identified in the teachers' stories knowledge from their own trajectories, we have understood the influences of the various moments and contexts of formation and work they have lived in the construction of their knowledge, we have established relationships between these knowledge, the formation received and the personal aspects of the teachers , and between training, the purposes of teaching Physical Education in the 1980s and 1990s and the characteristics of the students of the early years. The identified elements - with consideration for the time and space of training and professional performance of the participants - evidenced the process of building their knowledge throughout their life and profession trajectories, indicated successes and difficulties in their actions and contributed to reflect on the guidelines that we systematize for the initial training courses in Physical Education and, therefore, for the public policies of teacher training. As final considerations, we affirm that the life histories of the teachers indicated elements that contribute to reflect on the professional practice of teaching in Physical Education in the initial years, through the purposes of teaching, the characteristics of the students and the training gaps. These elements should therefore be considered and guaranteed in teacher training in order to meet the demands of the profession and to stimulate new studies based on this type of approach, on successful trajectories and teachers.
Keywords: Histórias de vida de professores de educação física; Saberes e identidades docentes; Anos iniciais do ensino fundamental; Life stories of physical education teachers; Knowledge and teaching identities; Early years of elementary education; CIENCIAS HUMANAS::EDUCACAO